An exploration of midwifery students’ perceptions of clinical facilitators and experiences of clinical facilitation during midwifery clinical placements in Perth, Western Australia - Cornell, Peta Kathleen (Curtin University, 2022)
Clinical facilitation is a model of supervision for students during professional practice experiences, with little known about this important aspect of midwifery education. A qualitative descriptive exploratory approach with thematic analysis was used to develop knowledge and understanding of undergraduate midwifery students’ experiences with such supervision in Western Australia. Midwifery clinical facilitation was highly valued by midwifery students. Respondent insights and recommendations will be instrumental in further developing and enhancing midwifery models of clinical supervision.